Commencement - Sullivan, J. Courtney (New York : Alfred A. Knopf, 2009)
This is a novel about Smith College classmates and their later lives.
Keywords: Women college students -- Fiction; Female friendship -- Fiction; Young women -- United States -- Social conditions -- Fiction